2012
DOI: 10.5539/gjhs.v4n6p148
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities of US and Arab Collaborations in Health Services Research: A Case Study from Qatar

Abstract: Economic globalization and advances in technology have made it more feasible and even necessary to develop international research collaborations in global public health. Historically, collaborations in global research described in the literature have been mostly “North-South” collaborations in which the more developed “North” country works together with a developing “South” country to conduct research in the latter. This type of collaboration has for the most part, represented unequal partnership and rarely le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Items for inclusion in a survey are built upon previously collected qualitative data that generate hypotheses or identify constructs or language used by research participants. For example, in a project involving the cultural adaptation of the Consumer Assessment of Healthcare Providers and Systems (CAHPS) survey for use in the Arabian Gulf (Hammoud et al 2012), baseline qualitative interviews identified new domains of importance such as gender relations, diet, and interpreter use not found in the existing CAHPS instrument. In addition, phrases participants used during the interviews informed the wording of individual items.…”
Section: Integration At the Methods Levelmentioning
confidence: 99%
“…Items for inclusion in a survey are built upon previously collected qualitative data that generate hypotheses or identify constructs or language used by research participants. For example, in a project involving the cultural adaptation of the Consumer Assessment of Healthcare Providers and Systems (CAHPS) survey for use in the Arabian Gulf (Hammoud et al 2012), baseline qualitative interviews identified new domains of importance such as gender relations, diet, and interpreter use not found in the existing CAHPS instrument. In addition, phrases participants used during the interviews informed the wording of individual items.…”
Section: Integration At the Methods Levelmentioning
confidence: 99%
“…served as co-principal investigator on a multistage, mixed methods parent study in Qatar to develop a health care quality assessment instrument that was adapted for populations whose native languages were Arabic, English, Hindi, and Urdu. 44 A theoretical model, Cultural Construction of Clinical Reality developed by Kleinman et al, 45 guided the research. During the first stage of qualitative data collection, Qatari team members expressed concern about how potential participants would respond to recruitment strategies dictated by US-based institutional review boards.…”
Section: Unstructured and Structured Field Observationsmentioning
confidence: 99%
“…To date, no published study has compared response rates of surveys conducted in person versus by mail, nor has any study reported participants’ preferred procedure of data collection or preference for reminders in Qatar or the Middle East. Few studies suggest strategic methods to help recruit participants in a multicultural context [ 26 , 35 ]. One generally useful strategy is to hire research assistants (RAs) who reside in-or have built trust with-the community, or who have the same cultural background as the potential participants [ 2 , 3 , 5 , 23 , 25 , 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Community-based research and research networks are not yet well-established in Qatar; moreover, research awareness is relatively new in this highly linguistically and culturally diverse society [ 35 ]. Understanding the pros and cons of different recruitment strategies is particularly important in Qatar, where postal addresses are mainly work addresses or personal post office (PO) boxes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation